PANDEMI DAN KAPITALISME SEBAGAI SEBUAH RESIKO - Ghebi Parwati; Anjelina Putri Aisyah; Muhamad Imam Prabowo (Yayasan Literasi Sains Indonesia, 2023)
Risk is one thing that we cannot know for sure when it will attack us. Risk, in essence, has the power to be present in aspects of our lives, when we cannot manage all the bad possibilities that we are facing. Current life, where the modern era has occurred since the last few decades, makes the possibility of greater risk. The increasingly complex aspects of human life make modern society vulnerable to risks. Both risks that have small or large impacts such as global risks, still both have a significant impact. In the current era, recently the world has been faced with a pandemic for approximately one year. What is the form of a pandemic as a risk and how is the current state of the world which is faced with a culture of capitalism, which is a risk for society today. In this research, we will discuss the pandemic which is a global risk and also the new flow of capitalism that threatens the global community regarding the uncertainties they must face. The complexity of the patterns of people's lives that are increasingly diverse must be properly addressed, in the midst of threatening uncertainty, people must be able to try to maintain the security of their lives. This study uses a literature review method. The results of the research show that the pandemic as a global risk has had an impact on many aspects, and the current capitalist system has made the global situation more vulnerable to risks.